PENGUKURAN DAN PENDUGAAN EROSI PADA LAHAN PERKEBUNAN KELAPA SAWIT DENGAN KEMIRINGAN BERBEDA - Ardianto, Kiki; Amri, Al Ikhsan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to determine the amount of erosion in oil palm plantations in various slopes and determine the extent of erosion in oil palm plantations. This research was conducted in oil palm plantations PT. Chemical Tirta Utama, conducted over four months from December 2015 to March 2106. The study was conducted by two methods, namely the methods of measurement and prediction of erosion. Measurements of erosion are conducted by placing small plots in the area gawangan dead plant oil palm on land slope of 9%, 19% and 31%. Estimation of erosion performed using USLE method. The results showed that the amount of soil erosion in oil palm plantations using small plots highest on the slope of 9%, amounting to 5.38 tonnes / ha, whereas the lowest on slopes of 31% amounting to 2.83 tonnes / ha. For the method of soil erosion USLE highest on the slope 31% ie 431.98 tons / ha, whereas the lowest on the slope of 9% is 386.55 tons / ha. The degree of erosion in oil palm plantations by estimating method USLE at an inclination of 9%, 19% and 31%, respectively, are 11.64, 12.53 and 14.04 which are all included in the very high category. The level of erosion in oil palm plantations with small terraced plots measuring method at an inclination of 9%, 19% and 31%, respectively 0.16, 0.12 and 0.09 which are all included in the low category. Keywords: erosion, palm oil, small plots, the slope of the land, USLE